2008
DOI: 10.1017/s0143385707000430
|View full text |Cite
|
Sign up to set email alerts
|

Decay of correlations in suspension semi-flows of angle-multiplying maps

Abstract: We consider suspension semi-flows of angle-multiplying maps on the circle for Cr ceiling functions with r≥3. Under a Crgeneric condition on the ceiling function, we show that there exists a Hilbert space (anisotropic Sobolev space) contained in the L2 space such that the Perron–Frobenius operator for the time-t-map acts naturally on it and that the essential spectral radius of that action is bounded by the square root of the inverse of the minimum expansion rate. This leads to a precise description of decay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(102 citation statements)
references
References 22 publications
5
96
0
Order By: Relevance
“…In this section, we will collection some basic notions from [25]. Throughout this section, we denote R = (− 1 4 , 1 4 ) 2 and Q = (− 1 3 , 1 3 ) 2 .…”
Section: Anisotropic Sobolev Spacesmentioning
confidence: 99%
“…In this section, we will collection some basic notions from [25]. Throughout this section, we denote R = (− 1 4 , 1 4 ) 2 and Q = (− 1 3 , 1 3 ) 2 .…”
Section: Anisotropic Sobolev Spacesmentioning
confidence: 99%
“…In a very similar setting, when μ τ g is the Lebesgue measure, Tsujii essentially shows in [24] that for generic ceiling functions, one can construct a Hilbert space H with the above properties such that…”
Section: F Naudmentioning
confidence: 99%
“…Liverani [13] later extended this result to higher dimensional contact Anosov flows, overcoming the difficult issue of the low regularity of hyperbolic foliations. Using a pseudo-differential approach, Tsujii [24] showed that generic suspensions over uniformly expanding maps of the circle have exponential decay of correlations and went a step further by giving an asymptotic expansion with an explicit upper bound on the error term, involving the expansion rate of the flow. He recently obtained the same result [25], unconditionally, for contact Anosov flows.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the only partially hyperbolic transformations for which a local limit theorem is proved in the literature are the Anosov flows, in [Wad96] (the specific algebraic structure of flows makes it possible to reduce the problem to the study of Axiom A maps, which are uniformly hyperbolic). With the techniques of [Tsu05], it is probably possible to obtain it also for skew-products over uniformly expanding maps, for an absolutely continuous measure. Unfortunately, the main motivating example of our study, described in the next paragraph, is nonuniformly hyperbolic, and its invariant measure is singular.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our setting, the map T is an isometry in the fibers, and a spectral gap seems therefore difficult to obtain. Note that [Tsu05] manages to construct a space with a spectral gap for such maps, but under strong assumptions: the map T should be uniformly expanding, andμ should be absolutely continuous with respect to Lebesgue measure. These properties are unfortunately not satisfied in our setting, and we will thus have to work without a spectral gap (on the space X × S 1 ).…”
Section: Examplesmentioning
confidence: 99%